Cognitive representations of peripheral neuropathy and self‐reported foot‐care behaviour of people at high risk of diabetes‐related foot complications. Issue 1 (26th August 2013) - Perrin, B. M.; Swerissen, H.; Payne, C. B.; Skinner, T. C.
Abstract Aim The aim of this study was to explore the cognitive representations of peripheral neuropathy and self‐reported foot‐care behaviour in an Australian sample of people with diabetes and peripheral neuropathy. Methods This cross‐sectional study was undertaken with 121 participants with diabetes and peripheral neuropathy. Cognitive representations of peripheral neuropathy were measured by the Patients' Interpretation of Neuropathy questionnaire and two aspects of self‐foot‐care behaviour were measured using a self‐report questionnaire. Hierarchical cluster analysis using the average linkage method was used to identify distinct illness schemata related to peripheral neuropathy. Results Three clusters of participants were identified who exhibited distinct illness schemata related to peripheral neuropathy. One cluster had more misperceptions about the nature of peripheral neuropathy, one cluster was generally realistic about the nature of their condition and the final cluster was uncertain about their condition. The cluster with high misperceptions of their condition undertook more potentially damaging foot‐care behaviours than the other clusters (F = 4.98; P < 0.01). Conclusions People with diabetes and peripheral neuropathy have different illness schemata that may influence health‐related behaviour. Education aimed at improving foot‐care behaviour and foot‐health outcomes should be tailored to specific illness schemata related to peripheral neuropathy.